Atomic-scale structural characterization of grain boundaries in epitaxial Ge/Si microcrystals by HAADF-STEM. (1st April 2019) - Arroyo Rojas Dasilva, Yadira; Erni, Rolf; Isa, Fabio; Isella, Giovanni; von Känel, Hans; Gröning, Pierangelo; Rossell, Marta D.
Abstract: The atomic structure of grain boundaries in Ge micro-crystals grown on Si pillars for the fabrication of a monolithically integrated X-ray detector was studied by high-resolution high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM). Three different boundaries are found in Ge: Σ 3 111 coherent twin boundaries, Σ 3 112 incoherent twin boundaries, and Σ 9 122 and Σ 27 552 grain boundaries. They are described using the structural unit models containing single columns. Remarkably, we find for the first time a Σ 3 112 incoherent twin boundary exhibiting two different atomic structures; one symmetric and one asymmetric. Their co-occurrence is explained by the presence of a small step in the boundary plane and the introduction of dislocations. Likewise, the atomic structure of junctions formed by the interaction of twin boundaries which result in Σ 9 122 and Σ 27 552 grain boundaries is also revealed. Geometrical phase analysis is applied to map the strain fields at two triple junctions and to uncover the position of the dislocations. Graphical abstract: Image 1